A BUILDING AS A GARDEN - A GARDEN AS A HOUSE - Filipi, Viktor (European Scientific Journal, ESJ, 2014)
This paper discusses the issue of urban development in the near future from the perspective of garden design and landscape architecture. It is a response to the deteriorating situation related to the population growth and the human separation from nature. Attention is mainly devoted to a detail - a building. The author suggests a solution in the form of a house and a garden being combined. This paper describes the positive impacts of such a combination from the environmental, ecological, hygienic, and economic perspectives. Further, garden forms appropriate for this vision are presented. The solution is documented using a study created in cooperation of Filipi and Damec.